The Impact Of Smoking On School Students - Büyükyılmaz, Funda (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Smoking is an act that has already received a bad stigma in society and also smoking in medical studies is an act that harms health for both active and passive smokers. The research methodology used is descriptive correlational research which is to determine the relationship between the impact of smoking on knowledge. This research was conducted at Makassar High School. The number of samples in this study were 34, where these 35 students consisted of three classes, namely first grade: 13 students, second grade: 15 students, and third grade: 10 students, who met the inclusion and exclusion criteria. The results showed that of the 36 students who were respondents, 24 students (69.6) showed the negative impact of smoking on health and 12 students (30.4%) showed the positive impact of smoking on health. Research conclusions and experiments continue to come to prove the truth of what we know, namely that smoking can cause death and various diseases with greater rates that can be suffered by many smokers.